Identification of nanometer-scale compositional fluctuations in silicate glass using electron microscopy and spectroscopy. (September 2018) - Nakazawa, Katsuaki; Miyata, Tomohiro; Amma, Shin-ichi; Mizoguchi, Teruyasu
Abstract: Silicate glasses are indispensable for optical and photonics applications, and their properties are affected by phase-separated structures. Understanding the phase separation behavior inside the glasses is thus crucial for controlling their optical properties. Here, we attempt to identify the phase-separated structure inside silicate glass by high-angular annular dark field-scanning transmission electron microscopy (HAADF-STEM) combined with a multi-slice image simulation. In addition to the phase-separated structure, we also demonstrate that the identifications of the type and stage of the phase-separation are possible by the HAADF observation in combination with a phase separation simulation. Graphical abstract: Unlabelled Image